Magnetic resonance direct thrombus imaging: a novel technique for imaging venous thromboemboli - Kelly, James; Hunt, Beverley J.; Moody, Alan (Thrombosis and Haemostasis, 2003)
Invasive testing is now seldom required in patients with suspected venous thromboembolism (VTE). However, a corollary of noninvasive imaging is increased complexity as results are often yielded as probabilities rather than definitive answers and additional testing is frequently required following initial imaging. This creates a milieu in which misunderstandings and protocol violations are common, potentially leading to diagnostic errors. A highly accurate noninvasive imaging technique which allows immediate treatment decisions to be made is needed. Magnetic resonance direct thrombus imaging (MRDTI) is a novel technique which detects methaemoglobin in clot, allowing visualisation of thrombus without using intravenous contrast. It has two major advantages over conventional modalities which identify it as having the potential to fill this role. Firstly, direct visualisation of thrombus overcomes many of the pitfalls of conventional techniques, which have either identified thrombus as a filling defect or in terms of surrogates. Secondly, simultaneous imaging of the legs and chest allows a comprehensive assessment of thrombus load, minimising the importance of overlooked subsegmental pulmonary embolism (PE) and potentially facilitating more titrated treatment.Early data suggest MRDTI is highly accurate for the detection of both deep vein thrombosis (DVT) and PE, and ongoing outcome studies are evaluating the safety of withholding treatment in suspected DVT and PE on the basis of negative MRDTI alone. If favorable, a multi-centre outcome study evaluating cost-effectiveness as well as safety would be justified. Subject to further evaluation, this technique has the potential greatly to simplify and standardise the investigation of suspected VTE.
Keywords: Magnetic resonance direct thrombus imaging; deep vein thrombosis; pulmonary embolism